Flexural mechanism and design method of novel precast concrete slabs with crossed bent-up rebar. (1st June 2022) - Chen, Ying; Shi, Hai-Rong; Wang, Chun-Lin; Wu, Jing; Liao, Zhi-Qiang
Abstract: Precast concrete slabs are one of the most widely used types of structural member in building industrialization. In this paper, a novel precast concrete slab with crossed bent-up rebar was proposed, where the rebar of precast concrete units was bent-up and embedded crossways in cast-in-place concrete toppings, forming a novel joint configuration of precast concrete slabs. The effects of two bent-up angles of the rebar in the precast concrete units, different thicknesses of the cast-in-place concrete toppings, and different reinforcement ratios on the failure modes of novel precast concrete slabs were studied using flexural loading tests with eight specimens. The failure modes of the specimens changed from the joint failure to the failure of the termination section of lap-splice rebar (TSLSR), when the horizontal angle of the bent-up rebar changed from 90 to 60°. Bent-up ends with an angle of 60° prevented the joint failure of the novel precast concrete slabs, and strengthened the flexural performance of the joint. The horizontal component force of the bent-up ends markedly strengthened the flexural capacity of the joint, and the vertical component force of the bent-up ends made the precast concrete units connect tightly with the cast-in-place concrete toppings, enhancing the anchorage effectiveness of the lap-splice rebar. There were two primary failure modes of the specimens: joint cracking caused by the yield of the lap-splice rebar in the joint, and plastic cracking failure of the section beyond the TSLSR. Finally, the design equations of the flexural capacity of the joint and the anchorage length of the bent-up ends were established, and the design process of the novel precast concrete slabs was given. Highlights: Proposing and testing a novel precast concrete slab with crossed bent-up rebars. Analyzing the force transfer mechanism of joints of the novel precast concrete slabs. Summarizing the main failure modes of the novel precast concrete slabs. Establishing the design equations and design process of the novel precast concrete slabs.